Agricultural mechanization in an oligarchic rural society: Central Chile, ca. 1840-1915 (Quinto Sol, 2023)
This article examines the development of mechanization in the hacienda system of Central Chile, an oligarchic rural society in a peripheral country, by discussing the role and interests of the main social and institutional actors involved in the introduction and diffusion of agricultural machinery. Mechanization was implemented from power by dominant actors in the Chilean economy, above all the large landowners, and the foreign commercial firms that imported machinery. Thus, it concentrated on the harvests of wheat, alfalfa and clover, the main commercial crops on Central Chile’s haciendas. In addition, mechanization consisted in the diffusion of imported machines and implements. The incipient Chilean metal industries (foundries) were not able to develop as significant producers of agricultural equipment. Despite their contradicting interests, those actors, along with state agricultural institutions’ experts, formed a knowledge elite that not only adopted but, more fundamentally, selected and creatively adapted those types and models of agricultural machines that demonstrated to be more suitable to the hacienda system.
Keywords: Central Chile; mechanization; hacienda system; machinery